The effect of single aortic cross-clamp technique versus multiple clamp technique on postoperative stroke in octogenarians undergoing coronary artery bypass grafting - Tekin, Esra Erturk; Balli, Mehmet; Yesiltas, Mehmet Ali; Uysal, Ayhan (Clinics Cardive Publ Pty Ltd, 2022)
Aim: In this study, we aimed to investigate the effect of the single aortic cross-clamp technique (SCT) (aortic cross-clamp only) versus the multiple-clamp technique (MCT) (aortic cross-clamp + side-biting clamp) on postoperative stroke in octogenarians undergoing coronary artery bypass grafting (CABG). Methods: A total of 171 patients aged 80 years and older who underwent isolated CABG were retrospectively analysed. The patients were divided into two groups according to the technique used during surgery: group 1 (n = 88) received the SCT, and group 2 (n = 83) received the MCT. Postoperative stroke was evaluated. Results: Of the patients, 127 were men and 44 were women. The mean age was 83.05 +/- 8.81 years in group 1 and 82.14 +/- 8.92 years in group 2. There was no statistically significant difference in the rate of postoperative stroke between the two techniques (p > 0.05). Conclusion: Postoperative stroke in octogenarians may result from not only the cross-clamp technique used but also several other factors. We found that both techniques yielded similar outcomes.
Keywords: octogenarians; aortic clamping; stroke; coronary artery bypass grafting